2004
DOI: 10.1007/bf02382824
|View full text |Cite
|
Sign up to set email alerts
|

Ag6Mo10O33 — a new silver ion conducting ammonia sensor material

Abstract: Abstract. Electrical and gas sensing properties of Ag6Mo10033 are investigated for the first time. Wagner's polarization experiment carried out on this material shows that it is a good silver ion conductor in the temperature range of 533 to 657 K. Studies show that it possesses good selectivity and sensitivity towards ammonia with fast response and retrace times indicating its potential as a sensor material for this gas below its TLV value. Morphological changes associated with this compound when exposed to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Here in Chemistry Group of IGCAR, one of the experiments conducted utilizes this setup is to find out the transport number of an ionic species in a compound [1]. This can be found out by passing a constant voltage for a specified duration and measure the resulting current characteristic of the sensor material.…”
Section: Methodsmentioning
confidence: 99%
“…Here in Chemistry Group of IGCAR, one of the experiments conducted utilizes this setup is to find out the transport number of an ionic species in a compound [1]. This can be found out by passing a constant voltage for a specified duration and measure the resulting current characteristic of the sensor material.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was pelletized and heated at 773 K in air for 24 hours. The Ag6MolO033 thick film preparation, characterization using XRD and gas sensing experiments are discussed in detail in our earlier publications [11,12]. AC impedance data of thick film were collected by two probe technique in the frequency range between 105 Hz and 100 Hz, with an applied Vnn s of 200 m V using AC impedance spectroscopy technique (Model SI 1260, Sol artron , UK) in presence of clean air and in presence of air containing analyte gas such as NH3 or H2 or PG were injected independently at 350°C.…”
Section: It Experimentalmentioning
confidence: 99%
“…Silver decamolybdate (Ag6MolO033) is a mixed ion conductor and it has been demonstrated to respond to trace levels of ammonia in air at 350°C by DC conductivity method [12]. This DC technique gives only information about the long range charge carrier migration (conductivity) of the sample and not about the short range charge carrier migration (or dielectric loss), which would be associated with localized rattling of charge carriers within cages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23] Besides, multiple oxidation states of molybdenum ions (Mo 3+ to Mo 6+ ), molybdates of metal or transition metal elements provide robust chemical stability (due to covalent bonding) and excellent ionic conductivity with respect to the electrolyte ions due to the conductive paths paved with metal or transition metal ions. [25,26] Recently, Mai et al [21] demonstrated the use of transition metal molybdates, i.e., CoMoO 4 in nanowire-like morphology as an electrode in pseudocapacitors with a specific capacitance of 62.8 F g −1 (at a current density of 1 A g −1 in a potential window of ΔV = 1 V), and further improved the capacitance to 187 F g −1 (at a current density of 1 A g −1 ) by forming heterostructure of MnMoO 4 /CoMoO 4 nanowires. Moreover, other transition metal molybdates, e.g., NiMoO 4 , [20,27,28] MnMoO 4 , [19,29] and BiMoO 4 , [30] in various morphologies have also been demonstrated as prospective pseudocapacitive electrode materials in supercapacitors.…”
mentioning
confidence: 97%